Effect Size Analyses of Souvenaid in Patients with Alzheimer’s Disease - Cummings, Jeffrey (J Alzheimers Dis, 2016)
Background: Souvenaid(®) (uridine monophosphate, docosahexaenoic acid, eicosapentaenoic acid, choline, phospholipids, folic acid, vitamins B12, B6, C, and E, and selenium), was developed to support the formation and function of neuronal membranes. Objective: To determine effect sizes observed in clinical trials of Souvenaid and to calculate the number needed to treat to show benefit or harm. Methods: Data from all three reported randomized controlled trials of Souvenaid in Alzheimer’s disease (AD) dementia (Souvenir I, Souvenir II, and S-Connect) and an open-label extension study were included in analyses of effect size for cognitive, functional, and behavioral outcomes. Effect size was determined by calculating Cohen’s d statistic (or Cramér’s V method for nominal data), number needed to treat and number needed to harm. Statistical calculations were performed for the intent-to-treat populations. Results: In patients with mild AD, effect sizes were 0.21 (95% confidence intervals: –0.06, 0.49) for the primary outcome in Souvenir II (neuropsychological test battery memory z-score) and 0.20 (0.10, 0.34) for the co-primary outcome of Souvenir I (Wechsler memory scale delayed recall). No effect was shown on cognition in patients with mild-to-moderate AD (S-Connect). The number needed to treat (6 and 21 for Souvenir I and II, respectively) and high number needed to harm values indicate a favorable harm:benefit ratio for Souvenaid versus control in patients with mild AD. Conclusions: The favorable safety profile and impact on outcome measures converge to corroborate the putative mode of action and demonstrate that Souvenaid can achieve clinically detectable effects in patients with early AD.